Zirconium carbide, hafnium carbide and their ternary carbide nanoparticles by an in situ polymerization route1. Issue 46 (23rd May 2015) - Yan, Chunlei; Liu, Rongjun; Zhang, Changrui; Cao, Yingbin
<x xml:space="preserve">Abstract</x> An in situ polymerization route for the synthesis of zirconium carbide, hafnium carbide and their ternary carbide nanoparticles.